The Role of Education in Shaping National Political Identity - Hadikusuma, Wira; Syafri, Fatrica; ., Musyaffa; Putra, Pebri Prandika (Journal of Ecohumanism, 2024)
The purpose of this study is to examine the development of national political education in PTKI Bengkulu as a preventive measure against the dangers of identity politics, especially ahead of the 2024 elections. This study aims to identify effective strategies for integrating identity politics discussion into national political education. This qualitative study employed basic data gathering techniques through direct interviews and documentation, as well as secondary data collection from social media, scientific journals, and news websites. Research data were then reduced, classified/classified, and methodological conclusions drawn. This study identifies two primary measures for the development of national political education at PTKI Bengkulu. First, curriculum integration involves incorporating discussion of identity politics into representative topics, particularly through National Political Education (PKN) and Panchasheel, sub-discussion education. This approach enables students to critically analyze identity politics in the context of national values and principles. Second, the organization of academic forums such as seminars, workshops, interactive talk shows, panel discussions, and debates facilitates open dialogue, critical thinking, and awareness of identity politics, fostering deeper understanding among students, educators, and the wider community. In conclusion, this study demonstrates the importance of national political education in mitigating risks associated with identity politics. By integrating identity politics discussions into the curriculum and organizing academic forums, PTKI Bengkulu can play an important role in promoting national unity and resilience. The results of this study provide valuable insights for academics, policymakers, and stakeholders in addressing the challenges posed by identity politics.